Stress management interventions for intensive and critical care nurses : a systematic review - Alkhawaldeh, Ja'far Mohammad Aqeel; Soh, Kim Lam; Mamat Mukhtar, Firdaus; Ooi, Cheow Peng; Anshasi, Huda A. (Wiley-Blackwell Publishing, 2020)
Background: The level of occupational stress of nurses working in intensive and critical care units is high. Although many studies have assessed the effectiveness of stress management interventions among intensive and critical care nurses, the methodological quality of these studies remains unclear.